Oligomeric aminoborane precursors for the chemical vapour deposition growth of few-layer hexagonal boron nitride. Issue 2 (8th December 2016) - Wang, Xiaochen; Hooper, Thomas N.; Kumar, Amit; Priest, Isobel K.; Sheng, Yuewen; Samuels, Thomas O. M.; Wang, Shanshan; Robertson, Alex W.; Pacios, Mercè; Bhaskaran, Harish; Weller, Andrew S.; Warner, Jamie H.
Abstract : Oligomeric aminoborane complexes are demonstrated as viable solid-state precursors for the chemical vapour deposition growth of few layered hexagonal boron nitride material. Abstract : We explore the use of stable, pre-formed, oligomeric aminoboranes as precursors for the chemical vapour deposition growth of few-layered hexagonal boron nitride (h-BN) films on Cu foils under atmospheric pressure conditions. Dimeric diborazane H3 B·NH2 BH2 ·NH3 (DAB), and trimeric triborazane H3 B·(NH2 BH2 )2 ·NH3 (TAB), derivatives of ammonia borane, H3 B·NH3 (AB), are compared with AB, a commonly used precursor for the CVD growth of h-BN. Both DAB and TAB show similar effectiveness to AB in growing h-BN few layered films. Using DAB as the precursor instead of AB leads to fully continuous h-BN films in a shorter period of time. Analysis of the surface of the h-BN films reveals that DAB and TAB precursors deposit more nanoparticles on the surface of the h-BN films during their CVD growth within the same time period as when using AB. The viability of these two new h-BN precursors (DAB and TAB), opens up a wider range of solid-state sources for growing wide band gap h-BN films using CVD techniques.